Kodek Baishiganuly’s Political Lyrics (Eurasian Journal of Philology Science and Education, 2024)
This article widely examines the work of the poet Kodek Baishiganuly, analyzes his political lyrics, in which his civic position is clearly manifested. Looking at the poet’s works, which reveal the reality of the period in which he lived, the truth and the historical events depicted in them are assessed, and the poet’s civil and political views are comprehensively differentiated. The poet’s skill in depicting the arbitrariness of Soviet power in the Kazakh steppe, including in the Alban country inhabited by Zhetysu, will be appreciated. In most of the poet's works, the truth of life of the colonized people is revealed through specific examples. The article analyzes in depth the lines of the poem that vividly describe the social contradictions that the poet saw with his own eyes and did not disappear from his consciousness. The poet's work provides evidence that the tough policies of the Soviet period in the twenties were not ignored. Together with the poet's poems, a scene of harsh years is considered, when the cattle of a rich village were swept out and exiled. Even the fact that some of them were shot as “enemies of the people” and that violence and unfair pressure caused public discontent is analyzed in detail. The incurable poet concludes that his sadness is caused by the ideals and interests of the country. The dramaturgy of the work is emphasized, expressing the bitter truth of society, expressing its despair and despair. The political campaigns of the twenties are analyzed in depth, boldly declaring that all political campaigns “killed the people with a merciless conspiracy.” Without leaving without attention a single sad moment in the life of the country, a step is being taken to show the legacy of the poet in a new light, presenting the life of the poet to the gaze of many.Key words: author, work, poetry, history, time, attitude, society.